Impact of physico-chemical characteristics on aquatic biodiversity of five prospected wetlands from Kipushi mining site in Haut-Katanga province in the Democratic Republic of the Congo - Mbale, Henri Kunzi; Mwamba, Marc wa Tshakapeta; Bongo, Gédéon Ngiala (Видавництво Львівської політехніки, 2023)
The development of mining industrialization is one of the factors that have favored the pollution of aquatic ecosystems. The main purpose of this study was to assess the influence of physico-chemical parameters of surface waters on the abundance of hydrophytes in 5 wetlands in Kipushi city, Haut-Katanga Province in DRC. Samples were collected from four rivers, of which: Kanyameshi, Kafubu, Kipushi, Kamarenge and Lake Kamarenge. The study used the presses for the preparation of herbariums as well as multifunction probe for physico-chemical analyses in situ and a spectrophotometer (415 nm) for some parameters. For environmental observations, the analysis of sediments allows to assess the pollution level by metallic trace elements, which breaks the ecological balance of this aquatic ecosystem. The abundance indices of plant species in each waterbody were subjected to a Factorial Component Analysis in order to identify the distribution of the elements of the dominant plant associations. Data analysis was performed using PAST software. The findings showed 29 species distributed in 26 genera, 13 families and 11 orders. The Confirmatory Factor Analysis showed the distribution of plant groupings following a gradient of mineralization of the zones as well as that of abundance-dominance. Physico-chemical parameters influence the distribution of hydrophytes in wetlands. They constitute indicators of toxicity having an adverse consequence on the aquatic ecosystem for these metallic elements are not biodegradable. The more there is accumulation of dissolved metals in water, the more they create an environmental hazard.
Keywords: invasive hydrophytes; physico-chemical parameters; impacts; kipushi mining city; DRC